APPROACH OF CO-MICRONIZATION IN SOLUBILITY ENHANCEMENT AND RELEASE PROFILE OF RAPID DISPERSIBLE TABLETS OF TOLFENAMIC ACID - ANAND, CHINMAY (Journal of Drug Delivery and Therapeutics, 2012)
Tolfenamic Acid is an orally and parenterally administered Non – steroidal anti-inflammatory drug belonging to the fenamate group. Dissolution is the rate limiting step for the absorption of Tolfenamic acid due to its poor solubility. In order to improve the solubility of drug and its dissolution rate concept of co-micronization of Tolfenamic acid with diluents and surfactants was studied in present study. Tolfenamic acid was co-micronized with microcrystalline cellulose and surfactants as sodium Lauryl sulfate. One reference formulation was also manufactured with conventional method using non-micronized Tolfenamic acid with surfactants. The formulation was than evaluated for various physical and analytical properties of rapid dispersible tablets. Results obtained showed that there was a significant increase in dissolution rate of drug in first 5 minutes of time interval as compare to reference formulation. The wetting and dispersion properties of formulation also found superior as compare to reference formulation.